2019
DOI: 10.1186/s12870-019-1867-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene identification and transcriptome analysis of low cadmium accumulation rice mutant (lcd1) in response to cadmium stress using MutMap and RNA-seq

Abstract: Background Cadmium (Cd) is a widespread toxic heavy metal pollutant in agricultural soil, and Cd accumulation in rice grains is a major intake source of Cd for Asian populations that adversely affect human health. However, the molecular mechanism underlying Cd uptake, translocation and accumulation has not been fully understood in rice plants. Results In this study, a mutant displaying extremely low Cd accumulation ( lcd1 ) in rice plant and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Cd contamination in rice grains has become a problem in China and other countries in Asia, mainly due to water and soil contamination 38 . It has been reported that knockout of OsNramp5 via CRISPR/Cas9 targeting exons 1, 7, and 9 or alteration of OsNramp5 on exon 7 via ethyl methanesulfonate drastically decreases Cd accumulation in rice grains, roots, and shoots, with or without significantly lowering the yield 39 42 . Our gene PAV analysis results revealed a 408-kb deletion on chromosome 7 that spans the entire OsNramp5 region in accessions Luohong3A and Luohong4A (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cd contamination in rice grains has become a problem in China and other countries in Asia, mainly due to water and soil contamination 38 . It has been reported that knockout of OsNramp5 via CRISPR/Cas9 targeting exons 1, 7, and 9 or alteration of OsNramp5 on exon 7 via ethyl methanesulfonate drastically decreases Cd accumulation in rice grains, roots, and shoots, with or without significantly lowering the yield 39 42 . Our gene PAV analysis results revealed a 408-kb deletion on chromosome 7 that spans the entire OsNramp5 region in accessions Luohong3A and Luohong4A (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such work has particularly focused on genes that encode either transporters, such as natural resistanceassociated macrophage proteins (NRAMPs) [18][19][20][21][22][23][24][25] , which mediate the entry of Cd from the rhizosphere, or those such as heavy metal ATPases (HMAs) [26][27][28][29][30][31][32] , which determine the deposition of Cd in vacuoles or its translocation in the plant. Significant findings include (i) that the level of NRAMP5 in rice may be linked to the higher uptake of Cd in this species than in maize 21 , (ii) combining knockout of one homeologous HMA4 gene (nonsense mutation) and reduction of the other (missense mutation) reduced Cd levels in tobacco, while maintaining plant vigour 27 , and (iii) the identification in wheat of HMA3 variants linked to reduced Cd accumulation 26 .…”
Section: Introductionmentioning
confidence: 99%
“…3000, which is also in agreement with other transcriptome projects in rice, where ca. 1000-3000 DEGs have been reported (e.g., Li et al, 2018;Cao et al, 2019;Chen et al, 2019;Sun et al, 2019). The response of the rice transcriptome is quite variable, depending on the organ, cultivar, and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%